2005
DOI: 10.1073/pnas.0507816102
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative high-throughput analysis of DNA methylation patterns by base-specific cleavage and mass spectrometry

Abstract: Methylation is one of the major epigenetic processes pivotal to our understanding of carcinogenesis. It is now widely accepted that there is a relationship between DNA methylation, chromatin structure, and human malignancies. DNA methylation is potentially an important clinical marker in cancer molecular diagnostics. Understanding epigenetic modifications in their biological context involves several aspects of DNA methylation analysis. These aspects include the de novo discovery of differentially methylated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
647
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(659 citation statements)
references
References 25 publications
(22 reference statements)
6
647
0
Order By: Relevance
“…Thus, quantitative assessment of DNA methylation is very important. 24,25,27,39,40 Our findings provide additional supporting evidence for molecular features of CIMP-low tumors different from CIMP-high and CIMP-0 tumors. CIMP-low tumors generally appear to methylate at multiple CIMP-specific CpG islands at low levels, whereas CIMP-0 tumors tend to show more loci with no evidence of methylation and CIMP-high tumors tend to show more loci with high-level methylation.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, quantitative assessment of DNA methylation is very important. 24,25,27,39,40 Our findings provide additional supporting evidence for molecular features of CIMP-low tumors different from CIMP-high and CIMP-0 tumors. CIMP-low tumors generally appear to methylate at multiple CIMP-specific CpG islands at low levels, whereas CIMP-0 tumors tend to show more loci with no evidence of methylation and CIMP-high tumors tend to show more loci with high-level methylation.…”
Section: Discussionsupporting
confidence: 67%
“…After the in vitro transcription, 0.06 mL RNase A was added to cleave the in vitro transcript. The mixture was diluted with ddH 2 O, dispensed onto silicon chips preloaded with matrix (SpectroCHIP; SEQUENOM, Inc.), and the mass spectra data were collected by the MassARRAY mass spectrometer (Bruker-SEQUENOM) [26].…”
Section: Pcr and Maldi-tof Mass Array Analysismentioning
confidence: 99%
“…Histology also revealed MA in testicular biopsy results obtained from 17 patients, who were defined as the MA group in this study. Although all MA patients lacked late spermatogenesis when examined histologically, an examination of ejaculate revealed that some had few spermatozoa in the ejaculate (MA4, 8,27), as shown in Tables 1 and 2. The mean ages of the control and MA groups (±s.d.)…”
Section: Characterization Of Patients By Histological Evaluationmentioning
confidence: 98%
“…27 This system analyzed base-specific cleaved amplification products. In this study, we used the MassARRAY Compact system (Sequenom).…”
Section: Maldi-tof Ms Analysismentioning
confidence: 99%